Is the Prosperity Gospel the Gospel? The Prosperity and Productivity Gospels in Africa - Barron, Joshua R. (Evangelical Review of Theology, 2023)
We know that some versions of the Prosperity Gospel are off the rails, as this article colourfully documents. But the article goes on to commend the positive impact of some African variants that often go unnoticed.
free